Identification of diagnostic signatures associated with immune infiltration in Alzheimer’s disease by integrating bioinformatic analysis and machine-learning strategies - Tian, Yu; Lu, Yaoheng; Cao, Yuze; Dang, Chun; Wang, Na; Tian, Kuo; Luo, Qiqi; Guo, Erliang; Luo, Shanshun; Wang, Lihua; Li, Qian (Frontiers in Aging Neuroscience, 2022)
Objective: As a chronic neurodegenerative disorder, Alzheimer’s disease (AD) is the most common form of progressive dementia. The purpose of this study was to identify diagnostic signatures of AD and the effect of immune cell infiltration in this pathology. Methods: The expression profiles of GSE109887, GSE122063, GSE28146 and GSE1297 were downloaded from the Gene Expression Omnibus (GEO) database to obtain differentially expressed genes (DEGs) between AD and control brain samples. Functional enrichment analysis was performed to reveal AD-associated biological functions and key pathways. Besides, we applied the Least Absolute Shrinkage Selection Operator (LASSO) and support vector machine-recursive feature elimination (SVM-RFE) analysis to screen potential diagnostic feature genes in AD, which were further tested in AD brains of validation cohort (GSE5281). The discriminatory ability was then assessed by the area under the receiver operating characteristic (ROC) curves (AUC). Finally, CIBERSORT algorithm and immune cell infiltration analysis were employed to assess the inflammatory state of AD. Results: A total of 49 DEGs were identified. The functional enrichment analysis revealed that leukocyte transendothelial migration, cytokine receptor interaction, and JAK-STAT signaling pathway were enriched in AD group. MAFF, ADCYAP1, and ZFP36L1 were identified as the diagnostic biomarkers of AD with a high discriminatory ability (AUC =0.850) and validated in AD brains (AUC =0.935). As indicated from the immune cell infiltration analysis, naive B cells, plasma cells, activated/resting NK cells, M0 macrophages, M1 macrophages, resting CD4+ T memory cells, resting mast cells, memory B cells, and resting/activated dendritic cells may participate in the development of AD. Additionally, all diagnostic signatures presented different degrees of correlation with different infiltrating immune cells. Conclusion: MAFF, ADCYAP1, and ZFP36L1 may become new candidate biomarkers of AD, which were closely related to pathogenesis of AD. Moreover, the immune cells mentioned above may play crucial roles in disease occurrence and progression.